KONTRIBUSI KONSEP PENDIDIKAN AKHLAK MENURUT UMAR BARADJA DALAM PENDIDIKAN ISLAM - Malik Fajar Setiawan (VICRATINA, 2022)
This study aims to describe the problem of the contribution of moral education according to Umar Baradja in Islamic education. The problem faced is to find out what roles can affect Islamic education from various aspects carried out by Umar Baradja. This research uses the content analysis method and the type of research used is library research, namely data collection or scientific writings that aim directly at the object of research or library data collection. Data collection is carried out by collecting data from various journals, articles, newspapers and printed books which will then be analyzed again. After analysis, then these elements are combined again to reach a conclusion.